2018
DOI: 10.1002/dev.21611
|View full text |Cite
|
Sign up to set email alerts
|

End‐state comfort in two object manipulation tasks: Investigating how the movement context influences planning in children, young adults, and older adults

Abstract: The movement context (pantomime, pantomime with image/object as guide, and actual use) has been shown to influence end-state comfort-the propensity to prioritize a comfortable final hand position over an initially comfortable one-across the lifespan. The present study aimed to assess how the movement context (pantomime, using a dowel as the tool, and actual use) influences end-state comfort when acting with objects (glass/hammer) that differ in use-dependent experience. Children (ages 6-11, n = 70), young adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 33 publications
(66 reference statements)
1
11
0
Order By: Relevance
“…As expected (e.g., Kuhtz-Buschbeck et al, 1998), significant differences in kinematic outcomes between the groups were found at each of the four movement phases investigated (onset latency, reach-to-grasp, grasp, transport-to-fit). In accordance with the suggested developmental trend for action organization (Jongbloed-Pereboom et al, 2013;Rosenbaum et al, ;Scharoun Benson et al, 2018;Stöckel et al, 2012;van Swieten et al, 2010;Wilmut & Byrne, 2014;Wunsch et al, 2016), less efficient movement organization related to task performance was found in the children than in the adults. More specifically, the 10-year-olds mainly differed from the adults regarding kinematic parameters associated with motor planning, whilst the 6-year-olds differed regarding parameters related to both motor planning and control.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…As expected (e.g., Kuhtz-Buschbeck et al, 1998), significant differences in kinematic outcomes between the groups were found at each of the four movement phases investigated (onset latency, reach-to-grasp, grasp, transport-to-fit). In accordance with the suggested developmental trend for action organization (Jongbloed-Pereboom et al, 2013;Rosenbaum et al, ;Scharoun Benson et al, 2018;Stöckel et al, 2012;van Swieten et al, 2010;Wilmut & Byrne, 2014;Wunsch et al, 2016), less efficient movement organization related to task performance was found in the children than in the adults. More specifically, the 10-year-olds mainly differed from the adults regarding kinematic parameters associated with motor planning, whilst the 6-year-olds differed regarding parameters related to both motor planning and control.…”
Section: Discussionsupporting
confidence: 80%
“…Improvements in goal‐directed upper‐limb movement organization have been suggested related to the development of motor planning (Simon‐Martinez et al, ), also supported by observations of a parallel developmental trajectory for motor planning abilities between 3 and 12 years of age according to the end state comfort effect (ESC; Jongbloed‐Pereboom, Nijhuis‐van der Sanden, Saraber‐Schiphorst, Crajé, & Steenbergen, ; Rosenbaum et al, ; Scharoun Benson et al, ; Stöckel, Hughes, & Schack, ; van Swieten et al, ; Wilmut & Byrne, ; Wunsch, Pfister, Henning, Aschersleben, & Weigelt, ). A few studies have investigated planning aspects within the framework of goal‐directed reach‐to‐grasp kinematics in children, although with some inconsistency.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…The current study aimed to increase knowledge of joint action object manipulation through the assessment of children, young adults (YAs), and older adults (OAs). Building upon Scharoun Benson, Roy, and Bryden’s (2018) work assessing independent manipulation, participants performed two joint action tasks (pickup and pass; pickup and pass for use) with two objects that differ in use-dependent experience (glass and hammer). Two movement contexts (demonstration with a dowel; actual object use) were assessed.…”
mentioning
confidence: 99%